The Influence of Store Atmosphere on Customer Satisfaction and Revisit Intention: A Study on Customers of Café Nakoa Malang - Eko Agus Susilo; Almer Rasyid; Dimas Septiono Tri Bagus Pamungkas (Jurnal Penelitian, 2025)
This study aims to analyze the influence of store atmosphere on customer satisfaction and revisit intention among consumers of Café Nakoa, Bethek branch, Malang City. The research is based on the growing trend of coffee shops in urban areas and the importance of creating a store atmosphere that enhances customers’ experiences. Store atmosphere is considered a key factor in shaping customer perception, comfort, and loyalty. This research uses a quantitative approach with an explanatory research type. Data collection was conducted through a questionnaire distributed to 90 respondents who were customers of Café Nakoa Bethek. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the help of SmartPLS 4 software. The variables studied include store atmosphere (X), customer satisfaction (Z), and revisit intention (Y). The results indicate that store atmosphere has a positive and significant influence on customer satisfaction and revisit intention. Moreover, customer satisfaction also significantly affects revisit intention. Another finding reveals that customer satisfaction mediates the indirect effect of store atmosphere on revisit intention. These results imply that optimizing store atmosphere can be a key strategy for enhancing consumer loyalty and business sustainability in the café industry.